2012
DOI: 10.1063/1.4717755
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red blood cell aggregation on velocity and cell-depleted layer characteristics of blood in a bifurcating microchannel

Abstract: Red blood cell (RBC) aggregation is a multifaceted phenomenon, and whether it is generally beneficial or deleterious remains unclear. In order to better understand its effect on microvascular blood flow, the phenomenon must be studied in complex geometries, as it is strongly dependent on time, flow, and geometry. The cell-depleted layer (CDL) which forms at the walls of microvessels has been observed to be enhanced by aggregation; however, details of the characteristics of the CDL in complex regions, such as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 58 publications
4
62
0
Order By: Relevance
“…Besides, an effective slip condition is commonly used for a variety of interface phenomena to represent the macroscale effects. For instance, microfluidic experiments have shown that red blood cells tend to create a cell-depleted layer near the wall, that also induces an apparent slip effect (Fåhraeus and Lindqvist 1931;Sherwood et al 2012). Gas flow through porous media under low Knudsen number might also be accurately characterized with an effective slip condition (Lasseux et al 2014).…”
Section: The Slip Boundary Conditionmentioning
confidence: 99%
“…Besides, an effective slip condition is commonly used for a variety of interface phenomena to represent the macroscale effects. For instance, microfluidic experiments have shown that red blood cells tend to create a cell-depleted layer near the wall, that also induces an apparent slip effect (Fåhraeus and Lindqvist 1931;Sherwood et al 2012). Gas flow through porous media under low Knudsen number might also be accurately characterized with an effective slip condition (Lasseux et al 2014).…”
Section: The Slip Boundary Conditionmentioning
confidence: 99%
“…By contrast, dispersion, deformation, and rotation of RBCs are induced at high-shear rate conditions. 1,2 The shear-thinning effect of blood viscosity is mainly attributed to these hemorheological characteristics of RBCs in plasma. Blood viscosity varies according to physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology followed was similar 162 to that previously described by Dusting et al [13] and Sherwood et al [50]. Images of 1280 × 384 pixels,…”
mentioning
confidence: 99%